Post mortem vitreous magnesium in adult population. (March 2018) - Tse, R.; Garland, J.; Kesha, K.; Morrow, P.; Lam, L.; Elstub, H.; Cala, A.D.; Palmiere, C.; Stables, S.
Highlights: Post mortem vitreous Mg was steady in the early post mortem period (1.03 mmol/L). No difference in post mortem vitreous Mg demonstrated between sexes. Post mortem vitreous Mg did not correlate with age in adult population. Post mortem vitreous Mg did not correlate with other vitreous electrolytes. Diabetics had higher post mortem vitreous Mg. Abstract: Background: The study of post mortem vitreous magnesium (Mg) is less common than sodium (Na), chloride (Cl) and potassium (K) in the forensic literature. There is no accepted normal range for post mortem vitreous Mg and the relationship between post mortem vitreous Mg levels and post mortem interval (PMI), other electrolyte levels, disease conditions, age and sex have not been fully established. Aim: To investigate the relationship of post mortem vitreous Mg with age, sex, PMI, vitreous electrolyte levels and diabetic status. Methods: A retrospective study of 20 consecutive cases of diabetics and 20 non-diabetic adult deaths was performed. Spearman correlation and the permutation test were used to explore the relationship between post mortem vitreous Mg and continuous and categorical variables respectively. Results: The mean post mortem vitreous Mg was 1.03 mmol/L (95%CI: 0.98–1.08 mmol/L). The absolute Spearman correlation coefficients (rho) between post mortem vitreous Mg with PMI, age, and other vitreous electrolytes (Na, Cl, and K) ranged between 0.04–0.21 (p > 0.19). Post mortem vitreous Mg was statistically higher in diabetics (mean difference: 0.08 mmol/L; area-under-the-curve = 0.65 on receiver-operator-characteristic curve). No statistical difference was demonstrated between sexes (p = 0.92). Conclusions: In our adult population, post mortem vitreous Mg did not correlate with age, PMI, other vitreous electrolytes (sodium, chloride and potassium) or sex. It was higher in diabetics, however had limited utility as a surrogate marker. Overall, post mortem Mg is steady in the early post mortem period with a mean of 1.03 mmol/L.